Anti-crack easy-to-construct mortar and preparation method thereof
By using materials such as epoxy modified vinylon fiber and modified bentonite in plastering mortar, the problems of easy cracking, poor flatness and poor construction properties of the mortar are solved, and higher crack resistance, flatness and construction are achieved Convenience.
Patent Information
- Application Number
- CN202411490347.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
Existing plastered mortars are prone to cracking, poor flatness and poor construction properties, which affect the beauty and service life of the building.
Epoxy modified vinylon fiber is used as the crack-resistant reinforcement material. Through the hydrophobicity and cross-linking reaction of epoxy halogenated alkylene modified vinylon fiber, it improves its dispersion and bondability in the mortar, and combines modified bentonite and specialty. Fine sand, optimize the composition of mortar.
It significantly improves the crack resistance, flatness, mechanical properties and construction properties of the mortar, enhances the overall stability and adhesion of the mortar, and improves the aesthetics and durability of the building.
Smart Images

Figure BDA0005099869070000081 
Figure BDA0005099869070000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a crack-resistant and easy-to-construct mortar and a preparation method thereof. Background Art
[0002] In the construction industry, plaster mortar is widely used for leveling and decoration of walls, floors and other building structure surfaces. However, existing plaster mortar often faces many problems, which not only affect the overall appearance of the building, but also reduce the service life of the building. The most common problems include easy cracking of the mortar, poor flatness and poor workability.
[0003] Since mortar shrinks during the hardening process, especially in a dry environment, the rapid evaporation of water will cause stress concentration inside the mortar, thus causing cracks. These cracks not only destroy the aesthetic appearance, but also may become water seepage channels, thus affecting the durability and safety of the building. In addition, during the construction process, traditional plastering mortar is often difficult to achieve the ideal flatness due to its lack of fluidity and uneven shrinkage in the later stage. The uneven surface not only affects the appearance, but also brings troubles to subsequent painting or tiling. Furthermore, some mortars are difficult to apply evenly during construction due to their high viscosity or poor rheological properties, and are prone to sagging or stratification, which increases the difficulty of construction.
[0004] Therefore, the above problems need to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a crack-resistant and easy-to-construct mortar and a preparation method thereof.
[0006] The technical solution adopted by the present invention is:
[0007] The present invention provides a crack-resistant and easy-to-construct mortar, comprising, by weight:
[0008] 100-130 parts of cement, 600-800 parts of fine aggregate, 20-30 parts of epoxy modified vinylon fiber, 120-180 parts of admixture, 0.6-0.8 parts of admixture;
[0009] The epoxy-modified vinylon fiber is obtained by modifying the vinylon fiber with an epoxy halogenated alkane;
[0010] The admixture comprises 70-90 parts of fly ash, 35-45 parts of modified bentonite and 15-45 parts of slag.
[0011] The present invention proposes a crack-resistant and easy-to-construct mortar. By adopting epoxy-modified vinylon fiber as the crack-resistant reinforcing material of cement mortar, the hydrophobicity of the vinylon fiber modified by epoxy halogenated alkyl is significantly enhanced, and its dispersibility in the mortar can be effectively improved; at the same time, the epoxy groups in the epoxy-modified vinylon fiber can also undergo a cross-linking reaction with the hydroxyl groups in the modified bentonite. By utilizing the good dispersibility of the modified bentonite, the epoxy-modified vinylon fiber can be more evenly dispersed in the mortar, promoting the hydrogen bonding effect between the -C-OH on its molecular chain and the -OH in the cement hydration product, thereby greatly enhancing the adhesion between the epoxy-modified vinylon fiber and the mortar, and improving the crack resistance, flatness, mechanical properties and construction performance of the mortar.
[0012] Preferably, the epoxy-modified vinylon fiber has a helical structure.
[0013] More preferably, the epoxy-modified vinylon fiber is obtained by surface-grafting vinylon fiber with epichlorohydrin under alkaline conditions and then twisting the surface.
[0014] More preferably, the mass ratio of the vinylon fiber to the epichlorohydrin is 1:0.5-0.7.
[0015] More preferably, the length of the vinylon fiber is 12-18 mm.
[0016] Preferably, the modified bentonite is obtained by modifying sodium-based bentonite with guar gum.
[0017] More preferably, the mass ratio of the guar gum to the sodium bentonite is 4-6:49-51.
[0018] Preferably, the fine aggregate is selected from ultra-fine sand with a fineness modulus of 0.64.
[0019] Preferably, the admixture is a mixture of a water retaining agent and an air entraining agent in a mass ratio of 2:2.5-3.5, wherein the water retaining agent is hydroxypropyl methylcellulose, and the air entraining agent is a mixture of sodium dodecylbenzene sulfonate and wood calcium powder in a mass ratio of 1:1.
[0020] On the other hand, the present invention provides a method for preparing the crack-resistant and easy-to-construct mortar as described in any of the above technical solutions, comprising the following steps: mixing cement, fine aggregate, epoxy-modified vinylon fiber, admixture, and additive according to a proportion to obtain the crack-resistant and easy-to-construct mortar. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further illustrated and described below through specific implementation methods.
[0022] An embodiment of the present invention provides a crack-resistant and easy-to-construct mortar, comprising:
[0023] 100-130 parts of cement, 600-800 parts of fine aggregate, 20-30 parts of epoxy modified vinylon fiber, 120-180 parts of admixture, 0.6-0.8 parts of admixture;
[0024] Epoxy modified vinylon fiber is obtained by modifying vinylon fiber with epoxy halogenated alkyl;
[0025] The admixture includes 70-90 parts of fly ash, 35-45 parts of modified bentonite and 15-45 parts of slag.
[0026] In a preferred embodiment of the present invention, the structure of the epoxy-modified vinylon fiber is a spiral structure. In the present invention, the epoxy-modified vinylon fiber adopts a spiral structure design, which can effectively alleviate the stress generated by cement during hydration shrinkage and the reaction to external forces, so that the prepared mortar has excellent crack resistance, and exhibits high flatness and tensile bonding strength, and the construction is more convenient.
[0027] In a more preferred embodiment of the present invention, the epoxy-modified vinylon fiber is obtained by surface grafting modification of the vinylon fiber with epichlorohydrin under alkaline conditions and then twisting. In the present invention, the epoxy halide is preferably epichlorohydrin, which is first used to modify the vinylon fiber. On the one hand, the introduction of epoxy groups can increase the hydrophobicity of the vinylon fiber and improve its dispersibility in the mortar, which is beneficial to its anti-cracking performance in the mortar. On the other hand, fine dents will appear on the surface of the vinylon fiber after the epichlorohydrin modification treatment, which increases the specific surface area of the vinylon fiber, improves the water retention of the vinylon fiber and the anti-cracking performance of the vinylon fiber in combination with the mortar; and then the modified vinylon fiber is designed with a spiral structure, and the setting of the special-shaped cross-section is more conducive to increasing the bonding effect between the fiber and the mortar, and improving the anti-cracking performance, flatness and other aspects of the mortar. In addition, the present invention has no particular limitation on the preparation method of epoxy-modified vinylon fiber. For example, the method can be as follows: put the vinylon fiber into deionized water 20-40 times its mass, add 10% sodium hydroxide solution to adjust the pH to 11-12, stir at 800-1200r / min for 10-20min, then add epichlorohydrin according to a certain mass ratio, continue stirring and reacting for 4.5-5.5h, filter, wash and dry after the reaction, then fix one end of the dried fiber on the motor and the other end on the clamp, and mechanically twist at a speed of 100r / min to obtain epoxy-modified vinylon fiber with a spiral structure.
[0028] In a more preferred embodiment of the present invention, the mass ratio of vinylon fiber to epichlorohydrin is 1:0.5-0.7. In the present invention, if the amount of epichlorohydrin is too high, due to the high activity of the epoxy group, excessive modification will cause the fibers to agglomerate, which is not conducive to their dispersion in the mortar; if the amount of epichlorohydrin is too low, the anti-cracking effect applied to the mortar is weak. For example, the mass ratio of vinylon fiber to epichlorohydrin can be any value of 1:0.5, 1:0.6, 1:0.7, etc., without special restrictions.
[0029] In a more preferred embodiment of the present invention, the length of the vinylon fiber is 12-18 mm. In the present invention, by controlling the length of the vinylon fiber to a suitable range, the effects of epichlorohydrin modification and twisting treatment are beneficial. For example, the length of the vinylon fiber can be any value of 12, 14, 16, 18 mm, etc., without particular limitation.
[0030] In a preferred embodiment of the present invention, the modified bentonite is obtained by modifying sodium-based bentonite with guar gum. In the present invention, the sodium-based bentonite is modified by guar gum, which can effectively improve the expansion performance of bentonite, enhance the water retention, adhesion and stability of the mortar, compensate for the shrinkage mortar, and improve its construction performance. At the same time, since the modified bentonite has a polyhydroxy structure, it is easy for the epoxy groups and hydroxyl groups in the epoxy-modified vinylon fiber to interact, which is more conducive to improving the dispersibility of the epoxy-modified vinylon fiber in the mortar, thereby further improving the overall stability, adhesion, flatness, crack resistance and construction performance of the mortar. In addition, the present invention has no particular limitation on the preparation method of the modified bentonite. For example, the preparation method can be as follows: guar gum is added to 80-125 times of its mass in 40°C deionized water, stirred at 100-300r / min at 60°C for 25-35min, then sodium bentonite is added according to a certain mass ratio, stirred at 200-300r / min at 70-80°C for 25-35min, and the supernatant is removed after standing at room temperature for 12-24h, and dried at 100-110°C for 23-25h, and passed through a 100-mesh sieve to obtain the modified bentonite.
[0031] In a more preferred embodiment of the present invention, the mass ratio of guar gum to sodium bentonite is 4-6:49-51. In the present invention, for example, the mass ratio of guar gum to sodium bentonite can be any value of 4:49, 4:50, 4:51, 5:49, 5:50, 5:51, 6:49, 6:50, 6:51, etc., without any particular limitation.
[0032] In a preferred embodiment of the present invention, the fine aggregate is selected from ultra-fine sand with a fineness modulus of 0.64. In the present invention, by controlling the fineness of the fine aggregate in the mortar base material, the cracking performance of the mortar can be reduced.
[0033] In a preferred embodiment of the present invention, the admixture is a mixture of a water retaining agent and an air entraining agent in a mass ratio of 2:2.5-3.5, wherein the water retaining agent is hydroxypropyl methylcellulose, and the air entraining agent is a mixture of sodium dodecylbenzene sulfonate and wood calcium powder in a mass ratio of 1:1. In the present invention, for example, the mass ratio of the water retaining agent to the air entraining agent can be any value of 2:2.5, 2:2.7, 2:3, 2:3.2, 2:3.5, etc., without any particular limitation.
[0034] On the other hand, an embodiment of the present invention provides a method for preparing a crack-resistant and easy-to-construct mortar as any of the above-mentioned technical solutions, comprising the following steps: mixing cement, fine aggregate, epoxy-modified vinylon fiber, admixture, and additive according to a proportion to obtain a crack-resistant and easy-to-construct mortar.
[0035] Some of the raw materials of the following embodiments and comparative examples are as follows:
[0036] Cement: density is 3.1g / cm 3 , bulk density is 1300kg / m 3 The initial setting time of cement is 2h, the final setting time is 5h, and it is cured for 28d under standard conditions of temperature 20±2℃ and relative humidity ≥95%. Its strength is measured to be 35.0MPa.
[0037] Fine aggregate: Extra fine sand with fineness modulus of 0.64.
[0038] Vinylon fiber: Vinylon fiber with a diameter of 60±5μm, a tensile strength of 7.0cN / dtex, an elongation of 18% to 23%, a Young's modulus of elasticity of 170cN / dtex, and a length of 12±1mm.
[0039] Fly ash: The specific surface area is 7200cm 2 / g of finely ground grade II ash.
[0040] Sodium bentonite: colloidal value is 92mL / 15g, montmorillonite mass fraction is 72.3%, blue absorption is 32g / 100g, swelling index is 16mL / 2g, pH value is 7, density is 2.782g / cm 3 .
[0041] Water-retaining agent: Hydroxypropyl methylcellulose with a number average molecular weight of 15,000 is used.
[0042] Air entraining agent: a mixture of sodium dodecylbenzene sulfonate and wood calcium powder in a mass ratio of 1:1.
[0043] Example 1
[0044] A crack-resistant and easy-to-construct mortar, comprising, by weight:
[0045] 100 parts of cement, 600 parts of fine aggregate, 20 parts of epoxy modified vinylon fiber, 150 parts of admixture (70 parts of fly ash, 35 parts of modified bentonite, 45 parts of slag), and 0.6 parts of admixture (the mass ratio of water-retaining agent to air-entraining agent is 2:2.5).
[0046] Among them, the epoxy-modified vinylon fiber is obtained by surface grafting modification of vinylon fiber with epichlorohydrin under alkaline conditions and then twisting it. The specific steps are as follows: put 12±1mm long vinylon fiber into deionized water 20 times its mass, add 10% sodium hydroxide solution to adjust the pH to 11, stir at 800r / min for 10min, then add epichlorohydrin 0.5 times the mass of vinylon fiber, continue stirring and reacting for 4.5h, filter, wash and dry after the reaction, and then fix one end of the dried fiber on the motor and the other end on the fixture, and mechanically twist at a speed of 100r / min to obtain epoxy-modified vinylon fiber with a spiral structure.
[0047] The modified bentonite is obtained by modifying sodium bentonite with guar gum. The specific steps are as follows: 4 parts by mass of guar gum are added to 500 parts by mass of deionized water at 40°C, stirred at 100 r / min for 25 minutes at 60°C, then 49 parts by mass of sodium bentonite are added, stirred at 200 r / min for 25 minutes at 70°C, left to stand at room temperature for 12 hours, and then the supernatant is removed, dried at 100°C for 23 hours, and passed through a 100-mesh sieve to obtain the modified bentonite.
[0048] The above-mentioned crack-resistant and easy-to-apply mortar is prepared by the following method, including the following steps: cement, fine aggregate, epoxy-modified vinylon fiber, admixture, and additive are mixed according to a proportion to obtain the mortar. When used, the crack-resistant and easy-to-apply mortar is mixed with deionized water at a mass ratio of 100:19-21.
[0049] Example 2
[0050] A crack-resistant and easy-to-construct mortar, comprising, by weight:
[0051] 115 parts of cement, 700 parts of fine aggregate, 25 parts of epoxy modified vinylon fiber, 150 parts of admixture (80 parts of fly ash, 40 parts of modified bentonite, 30 parts of slag), and 0.7 parts of admixture (the mass ratio of water-retaining agent to air-entraining agent is 2:3).
[0052] Among them, the epoxy-modified vinylon fiber is obtained by surface grafting modification of vinylon fiber with epichlorohydrin under alkaline conditions and then twisting it. The specific steps are as follows: put 12±1mm long vinylon fiber into deionized water 30 times its mass, add 10% sodium hydroxide solution to adjust the pH to 11, stir at 1000r / min for 15min, then add epichlorohydrin 0.6 times the mass of vinylon fiber, continue stirring and reacting for 5h, filter, wash and dry after the reaction, and then fix one end of the dried fiber on the motor and the other end on the fixture, and mechanically twist at a speed of 100r / min to obtain epoxy-modified vinylon fiber with a spiral structure.
[0053] The modified bentonite is obtained by modifying sodium bentonite with guar gum. The specific steps are as follows: 5 parts by mass of guar gum are added to 500 parts by mass of deionized water at 40°C, stirred at 200r / min at 60°C for 30min, then 50 parts by mass of sodium bentonite are added, stirred at 250r / min at 75°C for 30min, left to stand at room temperature for 18h, the supernatant is removed, dried at 105°C for 24h, and sieved through a 100-mesh sieve to obtain the modified bentonite.
[0054] The preparation method of the crack-resistant and easy-to-construct mortar is the same as that in Example 1.
[0055] Example 3
[0056] A crack-resistant and easy-to-construct mortar, comprising, by weight:
[0057] 130 parts of cement, 800 parts of fine aggregate, 30 parts of epoxy modified vinylon fiber, 150 parts of admixture (90 parts of fly ash, 45 parts of modified bentonite, 15 parts of slag), and 0.8 parts of admixture (the mass ratio of water-retaining agent to air-entraining agent is 2:3.5).
[0058] Among them, the epoxy-modified vinylon fiber is obtained by surface grafting modification of vinylon fiber with epichlorohydrin under alkaline conditions and then twisting it. The specific steps are as follows: put 12±1mm long vinylon fiber into deionized water 40 times its mass, add 10% sodium hydroxide solution to adjust the pH to 12, stir at 1200r / min for 20min, then add 0.7 times the mass of vinylon fiber epichlorohydrin, continue stirring and reacting for 5.5h, filter, wash and dry after the reaction, and then fix one end of the dried fiber on the motor and the other end on the fixture, and mechanically twist at a speed of 100r / min to obtain epoxy-modified vinylon fiber with a spiral structure.
[0059] The modified bentonite is obtained by modifying sodium bentonite with guar gum. The specific steps are as follows: 6 parts by mass of guar gum are added to 500 parts by mass of deionized water at 40°C, stirred at 300 r / min for 35 minutes at 60°C, then 51 parts by mass of sodium bentonite are added, stirred at 300 r / min for 35 minutes at 80°C, left to stand at room temperature for 24 hours, and then the supernatant is removed, dried at 110°C for 25 hours, and passed through a 100-mesh sieve to obtain the modified bentonite.
[0060] The preparation method of the crack-resistant and easy-to-construct mortar is the same as that in Example 1.
[0061] Comparative Example 1
[0062] The difference between this comparative example and Example 2 is that epoxy-modified vinylon fiber is not added. The other components and steps remain unchanged.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 2 is that an equal amount of vinylon fiber is used to replace the epoxy-modified vinylon fiber in Example 2. The other components and steps remain unchanged.
[0065] Comparative Example 3
[0066] The difference between this comparative example and Example 2 is that the epoxy-modified vinylon fiber in Example 2 is replaced by an equal amount of vinylon fiber modified only by epichlorohydrin. The other components and steps remain unchanged.
[0067] Comparative Example 4
[0068] The difference between this comparative example and Example 2 is that the epoxy-modified vinylon fiber in Example 2 is replaced by an equal amount of vinylon fiber that has only been twisted. The other components and steps remain unchanged.
[0069] Comparative Example 5
[0070] The difference between this comparative example and Example 2 is that no modified bentonite is added, and the other components and steps remain unchanged.
[0071] Comparative Example 6
[0072] The difference between this comparative example and Example 2 is that an equal amount of sodium bentonite not modified by guar gum is used to replace the modified bentonite in Example 2. The other components and steps remain unchanged.
[0073] Comparative Example 7
[0074] The difference between this comparative example and Example 2 is that the preparation method of epoxy-modified vinylon fiber is different, and the vinylon fiber is first twisted, and then the surface of the twisted vinylon fiber is grafted and modified by epichlorohydrin under alkaline conditions. The epoxy-modified vinylon fiber in Example 2 is replaced by an equal amount. The other components and steps remain unchanged.
[0075] The mortars prepared in Examples 1-3 and Comparative Examples 1-7 were subjected to performance tests, wherein the room temperature crack resistance of the mortar was tested using JC / T951-2005 "Test Method for Cement Mortar Crack Resistance"; the remaining indicators were tested according to GB / T 25181-2019. The results are recorded in Table 1.
[0076] Table 1 Test results
[0077]
[0078]
[0079] It can be seen from Table 1 that the crack-resistant and easy-to-construct mortar prepared in the embodiment of the present invention has good crack resistance, high flatness and tensile bonding strength, and is easier to construct; Comparative Example 1 is compared with the data of Example 2, and it can be seen that the crack-resistant and easy-to-construct mortar prepared by using epoxy-modified vinylon fiber has high bonding strength and compressive strength, good crack resistance, and low 28d shrinkage rate; Comparative Examples 2-4 and 7 are compared with the data of Example 2, and it can be seen that the crack-resistant and easy-to-construct mortar prepared by using epoxy-modified vinylon fiber obtained by mechanically twisting vinylon fiber modified by epichlorohydrin has high bonding strength and compressive strength. The mortar has a high water retention rate, good crack resistance and flatness, and a low 28d shrinkage rate. Comparison of the data of Comparative Examples 5-6 with those of Example 2 shows that the crack-resistant and easy-to-construct mortar prepared by using modified bentonite has high water retention, bonding strength, and compressive strength, good crack resistance and flatness, and a low 28d shrinkage rate. This is because the expansion performance and water retention performance of the guar gum-modified bentonite are improved to a certain extent, and the guar gum-modified bentonite interacts with the epoxy-modified vinylon fiber, which effectively improves the overall stability, bonding performance, and flatness of the mortar, and also enhances its crack resistance and improves its construction performance.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A crack-resistant and easy-to-construct mortar, comprising, by mass: 100-130 parts of cement, 600-800 parts of fine aggregate, 20-30 parts of epoxy modified vinylon fiber, 120-180 parts of admixture, 0.6-0.8 parts of admixture; The epoxy-modified vinylon fiber is obtained by modifying the vinylon fiber with an epoxy halogenated alkane; The admixture comprises 70-90 parts of fly ash, 35-45 parts of modified bentonite and 15-45 parts of slag.
2. The crack-resistant and easy-to-construct mortar according to claim 1, characterized in that: The epoxy-modified vinylon fiber has a helical structure.
3. The crack-resistant and easy-to-construct mortar according to claim 2, characterized in that: The epoxy-modified vinylon fiber is obtained by performing surface grafting modification on the vinylon fiber with epichlorohydrin under alkaline conditions and then performing twisting treatment.
4. The crack-resistant and easy-to-construct mortar according to claim 3, characterized in that: The mass ratio of the vinylon fiber to the epichlorohydrin is 1:0.5-0.
7.
5. The crack-resistant and easy-to-construct mortar according to claim 3, characterized in that: The length of the vinylon fiber is 12-18 mm.
6. The crack-resistant and easy-to-construct mortar according to claim 1, characterized in that: The modified bentonite is obtained by modifying sodium-based bentonite with guar gum.
7. The crack-resistant and easy-to-construct mortar according to claim 6, characterized in that: The mass ratio of the guar gum to the sodium bentonite is 4-6:49-51.
8. The crack-resistant and easy-to-construct mortar according to claim 1, characterized in that: The fine aggregate is selected from ultra-fine sand with a fineness modulus of 0.
64.
9. The crack-resistant and easy-to-construct mortar according to claim 1, characterized in that: The admixture is a mixture of a water retaining agent and an air entraining agent in a mass ratio of 2:2.5-3.5, wherein the water retaining agent is hydroxypropyl methylcellulose, and the air entraining agent is a mixture of sodium dodecylbenzene sulfonate and wood calcium powder in a mass ratio of 1:
1.
10. A method for preparing the crack-resistant and easy-to-apply mortar according to any one of claims 1 to 9, comprising the following steps: The cement, fine aggregate, epoxy modified vinylon fiber, admixture and additive are mixed uniformly according to the proportion to obtain the crack-resistant and easy-to-construct mortar.